For a given input value bbb, the function ggg outputs a value aaa to satisfy the following equation. a-7=3(b+2)a−7=3(b+2)a, minus, 7, equals

Question

For a given input value bbb, the function ggg outputs a value aaa to satisfy the following equation. a-7=3(b+2)a−7=3(b+2)a, minus, 7, equals, 3, left parenthesis, b, plus, 2, right parenthesis Write a formula for g(b)g(b)g, left parenthesis, b, right parenthesis in terms of bbb.

in progress 0
Nevaeh 2 weeks 2021-09-08T20:25:22+00:00 1 Answer 0

Answers ( )

    0
    2021-09-08T20:26:35+00:00

    Answer:

      g(b) = 3b +13

    Step-by-step explanation:

    The equation to be satisfied is apparently …

      a−7=3(b+2)

    Add 7 to both sides to get “a” as a function of “b”.

      a = 3(b+2) +7

    Now, we can simplify and write in the desired functional form:

      g(b) = 3b +6 +7 . . . . eliminate parentheses

      g(b) = 3b +13

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )